A Cross-layer QoS Management Framework for ZigBee Cluster-Tree Networks - Severino, Ricardo (2016)
Wireless sensor networks show great potential to successfully address the timeliness and energy-efficiency requirements of different cyber-physical system applications. Generally, these requirements span several layers of the stack and demand an on-line mechanism capable of efficiently tuning several parameters, in order to better support highly dynamic traffic characteristics. This work presents a cross-layer QoS management framework for ZigBee cluster-tree networks. The proposed framework carries out an on-line control of a set of parameters ranging from the MAC sub-layer to the network layer, improving the successful transmission probability and minimizing the memory requirements and queuing delays through an efficient bandwidth allocation at the network clusters. Through extensive simulations in a real datacenter monitoring application scenario, we show that the proposed framework improves the successful transmission probability by 10 %, and reduces the end-to-end delay by 94 %.